Promoting Learner Autonomy: The case of Moroccan secondary EFL teachers - OUSSOU, Said (International Journal of Language and Literary Studies, 2020)
Learner autonomy has been the concern of a number of researchers in English language teaching. The concept has begun life since the 1980s. It has been considered in the Moroccan EFL context among the priorities of education, which English language teachers try to implement in their classes. Studies revealed that there are correlations between learner autonomy and other variables related to learners, which makes autonomy a subject of interest and thus an ability that should be fostered. As such, the present study aims at investigating the extent to which secondary EFL teachers promote autonomy in their learners. To achieve this purpose, a quantitative research design was employed in the study, generating and analyzing quantitative data. Therefore, a sample of 96 (57 males and 39 females) EFL teachers completed the questionnaire. Drawing on the findings, it was found that EFL teachers promote learner autonomy to a great extent and that the results were conclusive among the teachers’ rates of levels of agreement and disagreement regarding the strategies for promoting learner autonomy. Thus, it is concluded that the study reported on the extent to which teachers employ a number of strategies to promote learner autonomy and that it does not necessarily mean that the study explained the degree to which teachers know how to implement those strategies, as this would be beyond the purpose of the present study.